Improved Extraction Chromatographic Materials for the Separation and Preconcentration of Metal Ions - (:unkn) unknown (My University, 2015)
Growing public health and safety concerns over the use of nuclear materials have increased the demand for improved methods for the separation and preconcentration of various metal ions from environmental and biological samples for subsequent determination. Historically, solvent extraction and ion-exchange have often been the methods of choice for these separations. Solvent extraction, however, is cumbersome and can generate substantial volumes of organic wastes. Ion-exchange, while less cumbersome, lacks adequate selectivity and requires careful control of pH for satisfactory separation. Moreover it is generally not compatible with acidic samples, such as are commonly encountered in the analysis of biological and environmental samples. Extraction chromatography (EXC) combines the selectivity of solvent extraction with the ease of operation of an ion-exchange column. Since its origins in the late 1950’s, a wide variety of EXC materials have been described, and a number of these materials are now commercially available. The performance of EXC materials is deficient in several important respects, however, including modest retention, physical stability, column efficiency, and metal ion sorption capacity. The objective of this work, therefore, is to address these deficiencies and thus, to produce improved extraction chromatographic materials. With this in mind, a systematic study of the effect of the properties of the solid support, the extractant, and the diluent on these characteristics of EXC materials has been undertaken. Four different approaches have been followed: incorporation of ionic-liquids into EXC materials to improve metal ion retention, extractant encapsulation in silica sol-gels to improve the physical stability, stagnant pore plugging to improve the chromatographic efficiency, and the use of polysulfone capsules to improve the capacity. Unexpectedly, the use of an ionic liquid as a diluent for a crown ether (CE) was not found to provide an EXC material capable of strontium ion retention greater than that achievable with a conventional octanol-based material employing the same extractant. Encapsulation of the crown ether in a sol-gel glass or a polysulfone capsule, however, was found to yield strontium sorbents with improved physical stability, strontium ion uptake, or column efficiency. Lastly, it was found that the chromatographic efficiency of commercially available EXC resins can be significantly improved simply by blocking the relatively inaccessible pores with an inert filler. All of these results represent important steps towards the development of commercially viable alternatives to existing extraction chromatographic materials.